2015
DOI: 10.1614/ws-d-14-00139.1
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget-Site Resistance to ALS Inhibitors in Waterhemp (Amaranthus tuberculatus)

Abstract: A waterhemp population (MCR) previously characterized as resistant to 4-hydroxyphenylpyruvate dioxygenase and photosystem II inhibitors demonstrated both moderate and high levels of resistance to acetolactate synthase (ALS) inhibitors. Plants from the MCR population exhibiting high resistance to ALS inhibitors contained the commonly found Trp574Leu ALS amino acid substitution, whereas plants with only moderate resistance did not have this substitution. A subpopulation (JG11) was derived from the MCR population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 25 publications
7
63
0
1
Order By: Relevance
“…No mutations were detected at Asp 376 , Arg 377 , and Gly 654 in our populations; however, amino acid substitutions at these latter codons are reported to confer additional types and levels of ALS resistance in other weed species Tranel et al 2016), unreported/novel mutations at different codons in the ALS gene, and non-target site resistance (i.e., a translocation-based mechanism) could be the mechanisms of resistance in the remaining ALS inhibitor-resistant populations detected in Nebraska and Kansas by Werle et al (2016a). Non-target site ALS resistance has been reported in common waterhemp by Guo et al (2015). Our future work includes development of high-throughput assays to characterize ALS mutations in shattercane and johnsongrass populations and to more thoroughly characterize putative structural variation at the 5′ end of the gene, where Ala 122 , Pro 197 , a Twenty-three johnsongrass plants from each population were exposed to imazethapyr, and 23 additional plants were exposed to nicosulfuron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No mutations were detected at Asp 376 , Arg 377 , and Gly 654 in our populations; however, amino acid substitutions at these latter codons are reported to confer additional types and levels of ALS resistance in other weed species Tranel et al 2016), unreported/novel mutations at different codons in the ALS gene, and non-target site resistance (i.e., a translocation-based mechanism) could be the mechanisms of resistance in the remaining ALS inhibitor-resistant populations detected in Nebraska and Kansas by Werle et al (2016a). Non-target site ALS resistance has been reported in common waterhemp by Guo et al (2015). Our future work includes development of high-throughput assays to characterize ALS mutations in shattercane and johnsongrass populations and to more thoroughly characterize putative structural variation at the 5′ end of the gene, where Ala 122 , Pro 197 , a Twenty-three johnsongrass plants from each population were exposed to imazethapyr, and 23 additional plants were exposed to nicosulfuron.…”
Section: Resultsmentioning
confidence: 99%
“…The Trp 574 Leu mutation was not detected in all R individuals of J-36 (Table 6), indicating that multiple ALS-resistance mechanisms may be present within this population. Multiple mechanisms of ALS resistance within a population have been reported (Guo et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the McLean field was treated with soil-and foliarapplied triazine herbicides for at least seven consecutive years (Hausman et al 2011), which likely increased the selection for triazine-resistant waterhemp. Guo et al (2015) reported that MCR contains both target and non-target-site mechanisms that confer resistance to ALS inhibitors. Reduced waterhemp control with glufosinate 14 DAT was attributed primarily to regrowth of treated plants (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Many weed species have been reported with enhanced metabolic resistance mediated by cytochrome P450s to various herbicide modes of action including ALS, acetyl Co‐A carboxylase (ACCase), photosystem II, and HPPD . Metabolic resistance in A. tuberculatus has been previously reported for ALS, photosystem II and HPPD herbicides, with different cytochrome P450 genes likely conferring HPPD resistance in different populations . 2,4‐D has been reported as an inducer of cytochrome P450 activity in plants both in vitro and in vivo , including the induction of demethylation and ring‐methyl hydroxylation of chlortoluron in tobacco ( Nicotiana tabacum ) cells .…”
Section: Discussionmentioning
confidence: 99%